Surveillance and care for confirmed and suspected patients with COVID-19 in general practice (CovidCare): study protocol for an observational trial - Hoffmann, Mariell; Stengel, Sandra; Forstner, Johanna; Baldauf, Annika; Laux, Gunter; Aluttis, Frank; Qreini, Markus; Engeser, Peter; Szecsenyi, Joachim; Peters-Klimm, Frank (BMC family practice, 2021)
A SARS-CoV-2 infection can lead from asymptomatic through to critical disease in a dynamic and unpredictable course within a few days. The challenge in outpatient monitoring the highly contagious COVID-19 disease during the ongoing pandemic is to filter severe courses followed by admission to hospital with the aim of preventing an overburdening of clinics. However, little is known of the effect of risk factors on the course of the infection of outpatient patients. To support general practices in managing high risk patients, we designed a COVID-19 surveillance and care tool (CovidCare). It includes an initial assessment of yet known risk factors and symptoms and a continuous telephone monitoring of signs and symptoms. This study aims to investigate the effects of different risk factors on the course of the COVID-19 disease, utilisation of different health care services and to gain insights into the utilisation of CovidCare in general practices.
Gesehen am 18.10.2021